2017
DOI: 10.3389/fphar.2017.00173
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin Attenuates Ocular Inflammation: In vitro and In vivo Studies

Abstract: To investigate the effects of gabapentin, a structural analog of γ-amino butyric acid (GABA), on the inflammatory response of lipopolysaccharide (LPS)-stimulated rabbit corneal cells (SIRC) and on endotoxin-induced uveitis (EIU) in rabbits. We investigated the LPS-induced expression of several inflammatory mediators, such as TNF-α, IL-1β, cPLA2, COX-2, and PGE2 in the SIRC cells with or without gabapentin treatment. Gabapentin treatment significantly (p < 0.05) attenuated cytokines production, cPLA2 activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 32 publications
(38 reference statements)
3
35
0
Order By: Relevance
“…Our observations are in good agreement with the results obtained by Choi et al (2012), who demonstrated increased COX-2 expression in gingival fibroblasts treated with LPS [10]. Similar findings were obtained by Anfuso et al (2017) for rabbit corneal epithelial cells [11]. Taking into account the changes in NO and COX-2 levels caused by induction of the ocular surface cells with LPS, we may suppose that these compounds are not necessarily involved in triggering inflammation.…”
Section: Discussionsupporting
confidence: 93%
“…Our observations are in good agreement with the results obtained by Choi et al (2012), who demonstrated increased COX-2 expression in gingival fibroblasts treated with LPS [10]. Similar findings were obtained by Anfuso et al (2017) for rabbit corneal epithelial cells [11]. Taking into account the changes in NO and COX-2 levels caused by induction of the ocular surface cells with LPS, we may suppose that these compounds are not necessarily involved in triggering inflammation.…”
Section: Discussionsupporting
confidence: 93%
“…H&E staining revealed marked inflammatory cell infiltration in the iris-ciliary body region and the posterior vitreous cavity 24 h after the intravitreal injection of LPS (Fig. 1b), and the mRNA levels of TNF-α, a well-known marker of ocular inflammation [23], were also significantly increased in the retina by LPS (Fig. 1c).…”
Section: Resultsmentioning
confidence: 99%
“…No. 539134) as described previously [13]. Briefly, cell monolayers were rinsed 3 times with cold PBS, and extracted for 30 min on ice.…”
Section: Ecm Proteins Analysis By Western Blottingmentioning
confidence: 99%